Neuroinflammation and aging: focus on experimental Alzheimer´s disease - Saravia, Flavia Eugenia (2019)
The incidence of metabolic disorders including obesity, diabetes and metabolic syndrome have seriously increased in the last decades. These diseases - with growing impact in modern societies - constitute major risk factors for neurodegenerative disorders such as Alzheimer´s disease (AD), sharing insulin resistance, inflammation and associated cognitive impairment. The dentate gyrus of the hippocampus- a neurogenic area associated with memory and learning processes- is a recognized target for diabetic alterations and neurodegeneration. We explored the hippocampal neurogenesis and its microenvironment (microglia, astrocytes, vascularisation and glucocorticoid influence) in different dysmetabolic scenarios provided by spontaneous or induced experimental models. We found astrogliosis, reactive microglia, and reduced vascular arborization in association with cognitive impairment and lower or disturbed neurogenic ability, even in young animals. These phenomena were accompanied by a insulin-resistant state in the hippocampus, an impaired response to insulin. In the context of Alzheimer´s disease (AD), hippocampal alterations have been well described in advanced stages of the pathology, when amyloid deposition, inflammation and glial activation occur, but less attention has been directed to studying early stages. The neurogenic capability, measured as DCX+ cells, was strongly diminished and associated to alterations in cell maturity in a transgenic mouse model of AD, at early stages, when no amyloid deposits are present. Microglia already exhibited mostly intermediate and ameboid morphology-suggestive of activated state-and less corresponding to the ramified phenotype. Microglia, is able to sense pathogens and but also react against metabolic insults through phagocytosis and the release of cytokines. A chronic microglia stimulation may contribute to a persistent inflammation that can precede the neurodegenerative process.